Singing behaviour in a client with traumatic brain injury: a conversation analysis investigation. Issue 8 (3rd August 2018) - Azios, Jamie H.; Archer, Brent
ABSTRACT: Background : Traumatic brain injury (TBI) is associated with pragmatic communication difficulties that lead to difficulty in social interaction. Research on conversation abilities in persons with TBI is limited, but has revealed unique patterns of behaviour that result in success or breakdown in conversation. Only a handful of studies have examined real-world conversations of persons with TBI to better understand how these behaviours might be motivated by conversation moves of partners. Aims : This study involved an exploration of a particular behaviour in a man with TBI, singing, to better understand the interactional environment, and goals associated with the behaviour. Methods & Procedures : Over 7 h of conversation data were videorecorded from 10 therapy sessions in which a man with TBI recurrently employed singing during conversation. Instances of singing were identified and transcribed according to principles of conversation analysis (CA). A total of 39 instances were included and analysed independently, focusing on explaining the sequential context of the device and the interactional work that was achieved. Outcomes & Results : Data analysis revealed four distinct sequences involving instances of singing. These included a normative sequence in which the participant inserted singing in ways similar to neurotypical speakers. The other three sequences comprised of unusual instances of singing that allowed the participant to nominate new topics, demonstrate disalignment, and close topics in conversation. Conclusions : CA revealed that the participant produced singing in response to the actions of his conversation partners. All sequences were jointly produced and dependent upon the conversation turns before and after the instance of singing. The findings suggest that conversational partners pursue various interactional agendas during conversation in therapy sessions and the participant uses singing to perform facework in this context.